Gender gaps, financial inclusion and social integration in Kakuma Refugee Camp, Kenya - Afrika Onguko Okello (Economies, 2025)
The integration or resettlement efforts aimed at self-reliance of refugees are requisite for their adaptation to social and economic shocks and consequently to their human development and contribution to economic growth. This study analyses the drivers of financial inclusion and social integration and estimates the respective gender gap among households in Kakuma Refugee Camp, Kenya. Based on a 2019 socio-economic survey dataset, the study constructs indices to reveal the extent of financial inclusion and social integration. Using the ordered logistic regression, factors such as earning wages, asset accumulation, food security, social capital, education, and access to information demonstrate significant explanatory power for financial inclusion and social integration. The Blinder-Oaxaca decomposition technique for measuring the gender gap reveals that women are significantly better off with respect to financial inclusion compared to men. These results suggest that gendered financial inclusive and social integration programs can build refugee self-reliance. Accordingly, government and development partners should promote gender-inclusive strategies for refugees in Kenya. This study contributes to the literature on refugee financial inclusion and social integration by offering gender-specific insights into their barriers and enablers in protracted displacement contexts.
Keywords: F22; J15; J18; O15; 330; development; financial inclusion; forced displacement; gender gap; refugees; social integration; Kenya